2020
DOI: 10.3233/rnn-201001
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Astragaloside IV regulates the HIF/VEGF/Notch signaling pathway through miRNA-210 to promote angiogenesis after ischemic stroke

Abstract: This article has been retracted, and the online PDF has been watermarked “RETRACTED”. A retraction notice is available at DOI: 10.3233/RNN-239001.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…Moreover, the results indicated that AS-IV alleviated hypoxia-induced pulmonary vascular remodeling in vitro and in vivo. Together with the results of a previous study (41), the present study suggested that the effects of AS-IV might be mediated via downregulation of Jagged-1/Notch-3/Hes-5 expression. Therefore, the present study indicated that AS-IV might display important therapeutic functions as part of the Radix Astragali Mongolici extract for the prevention and treatment of cardiovascular disorders, such as PAH.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the results indicated that AS-IV alleviated hypoxia-induced pulmonary vascular remodeling in vitro and in vivo. Together with the results of a previous study (41), the present study suggested that the effects of AS-IV might be mediated via downregulation of Jagged-1/Notch-3/Hes-5 expression. Therefore, the present study indicated that AS-IV might display important therapeutic functions as part of the Radix Astragali Mongolici extract for the prevention and treatment of cardiovascular disorders, such as PAH.…”
Section: Discussionsupporting
confidence: 87%
“…Liang et al. (2020) have reported that miRNA‐210 can regulate the expression of the HIF/VEGF/Notch pathway‐associated molecules and participate in the process of promoting angiogenesis after hypoxia. In previous research, the expression of VEGF is regulated by many miRNAs, and it is predicted by computer software that miRNA‐210 can regulate VEGF, which affects the process of angiogenesis (Hua et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In hypoxia, miRNA-210 promotes endothelial cells to form blood vessels by inhibiting the expression of the target gene ephrin A3 (Ivan et al, 2008). Liang et al (2020) have reported that miRNA-210 can regulate the expression of the HIF/VEGF/Notch pathway-associated molecules and participate in the process of promoting angiogenesis after hypoxia.…”
Section: Gsyrd Regulated Mirna-210 and Ephrin A3 Expressionsmentioning
confidence: 99%
“…Astragaloside IV (AS-IV) is the main active component of AR. Many studies have proven that AS-IV can promote neurogenesis and angiogenesis and improve neurological function [ 24 , 25 ]. In addition, AS-IV negatively modulates endoplasmic reticulum stress-mediated apoptosis in endothelial cells to inhibit the increase in BBB permeability induced by ischemia/reperfusion and decrease the brain infarction ratio [ 26 ].…”
Section: Discussionmentioning
confidence: 99%